Spontaneous retroperitoneal hemorrhage due to renal angiomyolipoma rupture. Case presentation - Tomas Lazaro Rodriguez Collar; Alfonso José Pérez Espinosa; María Luisa García Gómez (Universidad de Ciencias Médicas de La Habana, 2016)
Introduction: The renal angiomyolipoma is a benign and rare tumor that when breaking, cause a retroperitoneal hemorrhage. Objective: To present a new case of spontaneous retroperitoneal hemorrhage due to renal angiomyolipoma rupture, with emphasis in the diagnostic elements and therapeutics. Case presentation: Male patient, 53 years old, with antecedents of convulsive crises since infancy and high blood pressure, that arrives to Luanda´s Multiprofile Clinic, showing pain in the right side of abdomen, vomits and low-grade fever of two days of evolution. On physical examination revealed abdominal contracture in rights flank and iliac fossa and tachycardia. Blood analysis revealed a light leucocytosis, and form that which was suspected an acute abdomen of inflammatory visceral origin, deciding a performance of a diagnostic laparoscopy, in which was identified an extensive retroperitoneal hematoma, with right side predominance. Taking in account the patient hemodynamic stability, was determinate to make an abdominal contrasted computerized axial tomography, which shows a complex tumoral mass in the anterior surface of the right kidney, with cortex discontinuity and hematic collection in the surrounding area. An urgency laparotomy was performed; was found a broken tumor in the renal right side that required a total nephrectomy without complications. The patient evolved satisfactorily. A broken renal angiomyolipoma was point by the histopathology report. Conclusions: Although it is infrequent, has to take into account the possibility of the clinical debut of a renal angiomyolipoma with retroperitoneal bleeding, as part of the differential diagnostics of the acute surgical abdomen. Keywords: Kidney, broken renal angiomyolipoma, spontaneous retroperitoneal hemorrhage, acute surgical abdomen.